Mayer-Rokitansky-Kuster-Hauser Syndrome (MRKH) Patients Treated with Laparoscopic Neovaginal with The Davydov Procedure with Epidural Anesthesia: A Case Report - Hadrians Kesuma Putra; Amir Fauzi; Ratih Krisna; Aerul Chakra Alibasya; Aidyl Fitrisyah; Alia Desmalia (HM Publisher, 2021)
Introduction. MRKH syndrome is characterized by incomplete or absent of vaginal and uterine agenesis. Currently there are no official guidelines on the management of MRKH syndrome. This case report is about the operative management in MRKH patients by neovaginal with laparoscopic Davydov procedure. Case presentation. A 26-year-old woman admitted that she had never had a period, the patient admitted that her breasts began to grow at the age of 13, and the patient was planning to get married, and refused to take further planning. The patient then came back to the RSMH urogynecology clinic after marriage, from the examination it was found that the pubic hole was ± 0.5 cm deep, speculum examination could not be done, the uterus could not be palpable from the rectal toucher. From the ultrasound examination, it was found that both ovaries were within normal limits and suspected uterine hypoplasia. Hormone tests were within normal limits, with the following values: LH 27.01 mIU / mL, FSH 57.08 mIU / mL, Estradiol 10 pg / mL, Prolactin 5.94 ng / mL. Patients with a history of atrial septal defect (ASD) and ventricular septal defect (VSD) Conclusion. Treatment of MRKH syndrome patients is usually complex and requires multidisciplinary counseling, therapy, and management, so it is hoped that it can help patients to make a functional vagina. Further research and collaboration from various multidisciplinary make pregnancy in patients with MRKH syndrome, not impossible, along with current technological and scientific developments, the selection of surrogate mothers, and uterine transplantation is an option.